Disability Sports as a Psychological Well-Being Intervention Tool for Persons with Disabilities - Dyah Permatasari; Mayang Ayu Angelita Sari; Reza Asep Adi Purnomo (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
The purpose of this study was to find out the role of disability sports on the psychological well-being of persons with disabilities. The research method uses a literature review by searching the selected keywords, namely